ENHANCING THE ESG-FINANCIAL PERFORMANCE DYNAMICS: DOES AUDIT QUALITY MATTER? - Rosli, Siti Aisyah; Ismail, Rina Fadhilah; Ghuslan , Mohamad Iruwan; Mahmud , Nurfarizan Mazhani; Zawawi, Maizura Meor (International Journal of Accounting, Finance and Business, 2024)
This study explores the impact of Environmental, Social, and Governance (ESG) performance on a firm’s financial performance. Utilizing a sample of 49 companies from 2019 to 2023, with 245 firm-year observations, the research employs panel data estimations to explore the direct effects of ESG performance on financial metrics. The findings reveal that ESG performance significantly enhances Return on Equity (ROE), highlighting its potential to increase shareholder value through sustainable business practices. The study further examines the moderating role of Big Four auditors, finding that their presence weakens the positive relationship between ESG and ROE, possibly due to stricter reporting standards. To further validate the findings, a robustness test was also conducted using Return on Assets (ROA), which shows that ESG's influence on asset efficiency is not immediately significant, likely due to the longer time required for operational efficiencies to materialize. These findings contribute to the existing literature by offering fresh insights into how ESG initiatives affect financial performance in the Malaysian context, emphasizing the distinct impact on equity returns while suggesting that the benefits to asset efficiency may take longer to emerge. Additionally, the study highlights the critical role of audit quality in shaping the financial impact of ESG practices, indicating that the involvement of Big Four auditors can alter the effectiveness of ESG strategies on shareholder value.